Rigore e libertà - Cardani, Elena (1998)
Escuela media en Ecully, en cercanías de <Lyon>, por M. Gautrand.
Keywords: GAUTRAND, MANUELLE; ARQUITECTURA EDUCACIONAL; ESCUELAS SECUNDARIAS; CONSTRUCCION; MADERA